Effects of altitude on heart rate variability and performance in swimmers - Schmitt, L.; Hellard, P.; Millet, G.; Foulliot, J. P.; Richalet, J. P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The effects of altitude training on the autonomic nervous system are still debated (Grover et al, 1986). Heart rate variability (HRV) analysis is a well recognized method to assess changes in the autonomic nervous system activity and has been shown to be related to the fitness and the fatigue in trained athletes (Pichot et al, 2000). In trained athletes, the effects of altitude on HRV may be influenced by both the level of altitude and the training loads. The aim of this study was to compare the effects of similar training loads on HRV and performance in well trained swimmers at two different altitudes. Method Height national level male swimmers (age = 17.0 ± 1.8 yrs, weight = 67.0 ± 6.6 kg, height = 180.4 ± 7.2 cm, O2max = 60 ± 4.0 ml.min¯¹.kg¯¹) trained during 17 days at 1200 m altitude (T1200), then after 6 weeks of a moderate training at see level, reproduced the same training plan at 1800 m (T1800). Prior, during and after T1200 and T1800 indices of HRV, using Fourier transform, were calculated in resting supine and standing positions. Prior and after T1200 and T1800, swimming performance (2000 m freestyle) was measured at 1200 m altitude. V& Results Changes in HRV were different during T1200 and T1800 : total HRV energy was increased during T1200 (P<0.01) but not during T1800. The parasympathetic energy in resting supine position (HFSU) was increased at 1200 m (P<0.05) but not at 1800 m ; the sympathetic energy in standing position (LFST) was increased at 1200 m (P<0.05) but not at 1800 m. The performance was improved at 1200 m (pre test : 1470 ± 35 sec - post test : 1442 ± 45 sec ; P<0.01) but not at 1800 m (pre test : 1457 ± 37 sec - post test : 1459 ± 45 sec). Change in performance was correlated with the increase in total HRV energy (r = 0.68; P=0.09), the increase in HFSU (r = 0.82; P<0.05) and in LFST (r = 0.73; P=0.06). Discussion and conclusion The same training loads induced a positive effect on HRV (Figure 1) and performance at 1200 m altitude whereas the effects seemed negative at 1800 m. This negative effect can be interpreted as the consequence of a more important stress due to the interaction between a greater hypoxic stimulus and the same training loads (Grover et al, 1986). These results highlighted two opposite effects : the aerobic training lead to an increase in HFSU whereas hypoxia indices a decrease. Since changes in HRV are correlated with changes in performance capacity during altitude training camps. HRV analysis in altitude appears as a promising method of monitoring the interacting effects of hypoxia and training loads in trained subjects and may help to identify the subjects who benefits from this type of training (responders).